Paleosalinity and Paleoproductivity reconstruction based on Foraminifera Microfossil analysis: A case study of the Oyo Formation, Gunungkidul, Special Region of Yogyakarta, Indonesia - Ihstar Andin Nur Fatiq; Esti Solehatun; Sapto Kis Daryono (Journal of Earth and Marine Technology (JEMT), 2026)
The Oyo Formation in the Southern Mountains of Java represents a neritic carbonate succession rich in foraminifera. This study aims to reconstruct the paleosalinity and paleoproductivity of the Oyo Formation and to evaluate their implications for depositional conditions associated with organic matter preservation. The study was conducted through micropaleontological analysis of foraminifera from three measured sections representing the Sambipitu Formation and the lower and upper parts of the Oyo Formation in Gunungkidul Regency, Special Region of Yogyakarta. Paleosalinity was reconstructed based on the relative abundance of Orbulina universa and Globigerinoides sacculifer, while paleoproductivity was interpreted using the benthic foraminiferal epifaunal–infaunal (E/I) index. The resulting paleosalinity and paleoproductivity trends were tentatively compared with the global Middle Miocene eustatic sea-level curve of Haq et al. (1987) to evaluate the possible influence of relative sea-level fluctuations on depositional conditions. The results indicate that the Sambipitu Formation was deposited under normal marine conditions characterized by low organic matter supply and well-oxygenated bottom waters. The lower part of the Oyo Formation also records normal marine conditions, interrupted by a localized hypersaline event. The upper part of the Oyo Formation exhibits decreasing paleosalinity toward brackish conditions, accompanied by the lowest E/I index values, suggesting increased organic matter flux and relatively reduced bottom-water oxygenation. These environmental conditions may have favored enhanced organic matter preservation compared with the underlying intervals. The results provide a preliminary micropaleontological screening of depositional conditions that may be favorable for organic matter preservation and identify intervals that warrant further evaluation using complementary geochemical analyses.